2023
DOI: 10.1088/0256-307x/40/9/090501
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Thermoelectric Pump: Energy Harvesting beyond Seebeck and Pyroelectric Effects

Abstract: Thermal-electric conversion is crucial for smart energy control and harvesting, such as thermal sensing and waste heat recovering. So far, people are aware of two main ways of direct thermal-electric conversion, Seebeck and pyroelectric effects, each with different working mechanisms, conditions and limitations. Here, we report the concept of “Geometric Thermoelectric Pump”, as the third way of thermal-electric conversion beyond Seebeck and pyroelectric effects. In contrast to Seebeck effect that requires spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…We would like to make clear that, for energy harvesting, the DQD absorbs energy from the environment, such as phonons, photons, and magnons. [46][47][48][49][50][51][52][53][54] It has been demonstrated that the coherent driven and dissipative nonlinear resonator yields the phase transition, where the competition between drive, nonlinearity and dissipation leads to a photon jump. [27][28][29][30][31][32][33] When the DQD system is in equilibrium, as shown in Fig.…”
Section: Inelastic Transport Elastic Transportmentioning
confidence: 99%
“…We would like to make clear that, for energy harvesting, the DQD absorbs energy from the environment, such as phonons, photons, and magnons. [46][47][48][49][50][51][52][53][54] It has been demonstrated that the coherent driven and dissipative nonlinear resonator yields the phase transition, where the competition between drive, nonlinearity and dissipation leads to a photon jump. [27][28][29][30][31][32][33] When the DQD system is in equilibrium, as shown in Fig.…”
Section: Inelastic Transport Elastic Transportmentioning
confidence: 99%
“…[1][2][3] Phonon-thermoelectric transport stands at the intersection of mesoscopic physics and opens quantum systems, exploring topics such as thermoelectric energy conversion in phonon-thermoelectric devices [4,5] and quantum dot (QD) circuit-quantum-electrodynamics. [6][7][8] Recently, various quantum phenomena based on QDs subjected to voltage bias and temperature gradients have been explored, revealing stressing the influence of quantum coherence on electron and phonon transport. [9][10][11][12][13][14][15] Coherence offers a promising viewpoint for investigating non-equilibrium open quantum systems, providing valuable insights for both theoretical foundations and practical applications.…”
mentioning
confidence: 99%